2018
DOI: 10.1016/j.arthro.2018.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Biomechanics of All Suture Anchors: What We Know So Far

Abstract: All suture anchors (ASAs) have proven valuable for soft tissue to bone fixation. They have a small footprint and can be inserted in tight spaces where little bone is available. Additionally, more ASAs can be inserted in the same amount of bone than their larger predecessors, and this may improve the overall biomechanics of the repair construct through load sharing at multiple points of fixation. ASAs are more dependent on the cortical bone than the cancellous bone where they are inserted for fixation. Decortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…In this context, ASA are thought to be superior to conventional anchors because of their smaller footprint and through less bone removal during implantation. The results of this study provide evidence that, in the case of anchor pullout, ASA show a significantly smaller cortical defect compared to conventional anchor [3,10,11,19,21]. Moreover, this study confirms that the volume of the bone cavity induced by ASA pullout compared to conventional anchors is significantly smaller.…”
Section: Discussionsupporting
confidence: 75%
“…In this context, ASA are thought to be superior to conventional anchors because of their smaller footprint and through less bone removal during implantation. The results of this study provide evidence that, in the case of anchor pullout, ASA show a significantly smaller cortical defect compared to conventional anchor [3,10,11,19,21]. Moreover, this study confirms that the volume of the bone cavity induced by ASA pullout compared to conventional anchors is significantly smaller.…”
Section: Discussionsupporting
confidence: 75%
“…evaluated eight different AC reconstruction techniques in a biomechanical study, observing the best restoration of anatomy with suture anchor fixation in the base of the coracoid process; (vi) When 3.5 mm suture anchors were used, both coracoid and clavicle tunnels were created by 2.0 mm drill bit or Kirschner wire, which needed smaller clavicle holes than those required for the tendon graft or endobutton procedure, thus minimizing the possibility of intraoperative and postoperative fractures; (v) Hardware removal was unnecessary, and implant‐related complication was avoided, indirectly reducing the cost for family members and the national healthcare system. Numerous studies have confirmed the feasibility and effectiveness of suture anchor fixation to repair ACJ separation 2, 21, 25, 46–48 . Nevertheless, all shoulders were immobilized in a sling for 6 weeks to ensure native CC ligament healing and prevent reduction loss.…”
Section: Discussionmentioning
confidence: 99%
“…This technology offers the following important features: (i) Regardless of whether 3.5 (295 N) or 5.0 mm (331N) was used, two suture anchors provided comparable biomechanical strength compared with the native CC ligament complex of 589 N and had sufficient strength to withstand physiological loads and restore stability 12,44 ; (ii) Suture anchor implantation in the base of the coracoid process was easier and less dangerous for the neurovascular structures than passing a loop underneath the coracoid process 25 ; (iii) Jerosch et al 45 evaluated eight different AC reconstruction techniques in a biomechanical study, observing the best restoration of anatomy with suture anchor fixation in the base of the coracoid process; (vi) When 3.5 mm suture anchors were used, both coracoid and clavicle tunnels were created by 2.0 mm drill bit or Kirschner wire, which needed smaller clavicle holes than those required for the tendon graft or endobutton procedure, thus minimizing the possibility of intraoperative and postoperative fractures; (v) Hardware removal was unnecessary, and implant-related complication was avoided, indirectly reducing the cost for family members and the national healthcare system. Numerous studies have confirmed the feasibility and effectiveness of suture anchor fixation to repair ACJ separation 2,21,25,[46][47][48] . Nevertheless, all shoulders were immobilized in a sling for 6 weeks to ensure native CC ligament healing and prevent reduction loss.…”
Section: Technical Characteristics and Key Technologies Of This Studymentioning
confidence: 99%
“…The diameter of the ASA increases when tension is applied through pulling, allowing the anchor to lock beneath the inner cortex of the bone. [3][4][5][6] These implants are believed to be less invasive than traditional implants, and could therefore minimize anchor related complications such as secondary joint damage in case of implant loosening and migration. [7][8][9][10][11][12][13][14][15] Additionally, these implants are radiolucent, reducing artifacts in postoperative imaging.…”
Section: Introductionmentioning
confidence: 99%